Efek Terapi Adjuvan Gel Kolagen terhadap Kadar Matriks Metaloproteinase-8 Saliva pada Gingivitis Pasca Scaling Root Planing - Haria Fitri; Nila Kasuma; Hardisman Hardisman; Hirowati Ali (Journal of Pharmaceutical and Sciences, 2026)
Gingivitis is a reversible inflammatory condition of the gingival tissue without attachment loss, primarily caused by plaque accumulation, which can trigger an immune response. Matrix metalloproteinase-8 (MMP-8) is an enzyme that contributes to collagen degradation. Scaling and root planing (SRP) is the standard therapy; however, it may induce a transient inflammatory response and result in suboptimal tissue regeneration, thereby necessitating adjunctive therapy. This study aimed to evaluate the effect of adjunctive collagen gel therapy on salivary matrix metalloproteinase-8 levels in gingivitis. This experimental study employed a pre- and post-test control group design involving 50 subjects divided into five groups: healthy control, gingivitis treated with SRP, and gingivitis treated with SRP combined with 1%, 2%, and 4% collagen gel. Salivary MMP-8 levels were measured to assess the inflammatory response. Statistical analysis revealed that collagen gel at concentrations of 1% and 2% had a significant effect on MMP-8 levels. In conclusion, Collagen gel at 1% and 2% concentrations significantly modulated salivary MMP-8 levels, suggesting a potential role in the tissue remodeling phase following SRP.